Significance of RBP4 in patients with gestational diabetes mellitus: a case-control study of Han Chinese women. (February 2014) - Zhaoxia, Liang; Mengkai, Du; Qin, Fang; Danqing, Chen
Abstract The role of retinol binding protein 4 (RBP4) in insulin resistance was recently identified. Our study investigated the correlation between RBP4 levels with lipid and glucose metabolism in a case-control study of women with gestational diabetes mellitus (GDM). Between May 2008 and May 2010, 70 pregnant women (24–28 weeks gestation) were recruited, including 35 women with GDM and 35 healthy controls. Blood samples were collected prior to and after oral glucose tolerance tests (OGTT) to detect serum RBP4, insulin, glycated hemoglobin, triglyceride (TG) and total cholesterol (TC) levels; the insulin resistance index (HOMA-IR) was calculated. Serum RBP4 levels in the GDM group were significantly higher than the control group (22.9 ± 3.09 µg/ml versus 17.9 ± 3.91 µg/ml; p < 0.01). Insulin, TC and TG levels in the GDM group and the control group were all significantly higher than the control group (p < 0.05). Serum RBP4 levels in the GDM group were correlated with HOMA-IR, TG and blood glucose levels at 1 h and 2 h after glucose was administered (r = 0.49, 0.49, 0.52, 0.52, respectively; p < 0.01). In conclusion, serum RBP4 levels are elevated in GDM cases than controls. In addition, RBP4 correlates with abnormalities of insulin resistance, glucose and lipid metabolism.